The effects of health fatalism and cyberchondria on parents' childhood vaccine hesitancy - Sarpdagi, Yakup; Yigit, Muhammet Faruk; Aydin, Muhammet Ali; Karadeniz Sir, Derya; Ciftci, Necmettin; Sarpdagi, Sevgi; Yildiz, Metin (Bmc, 2026)
Background Vaccine hesitancy is a major public health problem on a global scale, where individual choices directly affect public health and increase the risk of re-spread of infectious diseases. In particular, parental indecision about childhood vaccinations leads to weakened community immunity, placing a serious burden on health systems. Today, the ease of access to digital information has led to increased health concerns and individuals develop cyberchondria behaviors in the process of online information seeking. At the same time, individuals'fatalistic beliefs about health may also affect their vaccination decisions. This study evaluates the effects of religious health fatalism and cyberchondria on parents' hesitancy regarding childhood vaccinations. Methods This descriptive and cross-sectional study was conducted with 535 parents of children aged 0-5 who visited a healthcare institution in Turkey between March and August 2024. Data were collected using a Personal Information Form, the Religious Health Fatalism Scale, the Vaccine Hesitancy Scale, and the Cyberchondria Severity Scale Short Form. Data analysis was performed using SPSS 27.0 and the Hayes PROCESS program. Results In this study, a significant positive relationship was found between vaccine hesitancy and religious health fatalism ((3 = 0.274, p < .001) and cyberchondria ((3 = 0.193, p < .001). In hierarchical regression, religious health fatalism ((3 = 0.298) and cyberchondria ((3 = 0.200) significantly predicted vaccine hesitancy and together explained 12.7% of the variance. Demographic variables did not contribute significantly to the model (p > .05). In the moderation analysis, cyberchondria was found to play a role in strengthening the relationship between religious health fatalism and vaccine hesitancy ((3 = 0.088, p = .011). Conclusions This study has revealed that health-related fatalistic beliefs and levels of cyberchondria may be associated with parents' vaccine hesitancy. The findings suggest that vaccine hesitancy may be influenced not only by a lack of information but also by individuals' belief systems and health-related concerns in the digital environment.
Keywords: Cyberchondria; Health Fatalism; Parents; Vaccine Hesitancy